Pengaruh Prenatal Yoga terhadap Kualitas Tidur pada Kehamilan - Amelia, Rini; Mardiana; Surahmi M, Sari; Padma Risanti, Suci (HEALTH CARE: JURNAL KESEHATAN, 2025)
Pregnancy is a physiological process that begins from conception to delivery. During pregnancy, physiological and psychological changes occur that contribute to sleep quality. Approximately 45–46% of pregnant women globally experience poor sleep quality, with the highest prevalence occurring in the third trimester. One effort to improve sleep quality in pregnant women in their third trimester is prenatal yoga. This study was conducted to examine the effect of prenatal yoga on sleep quality during pregnancy. This study used a pre-experimental, one-group pretest-posttest design, conducted from October to November 2025 at the Erna Wena BPM Padang. The study population consisted of all pregnant women in their third trimester at BPM Erna Wena. The sample was selected using purposive sampling, with 20 participants. The intervention consisted of prenatal yoga. The results showed an improvement in sleep quality for pregnant women after the intervention, with a p-value of 0.004. Prenatal yoga has a positive impact on sleep quality during pregnancy. This study is expected to serve as a reference for addressing sleep quality disorders during pregnancy. Further research with a longer duration and a larger sample size is recommended to strengthen the evidence of its effectiveness.